A magnetically separable and recyclable Ag-supported magnetic TiO2 composite catalyst: Fabrication, characterization, and photocatalytic activity. (1st May 2018) - Chung, Woo Jin; Nguyen, Dinh Duc; Bui, Xuan Thanh; An, Sang Woo; Banu, J. Rajesh; Lee, Sang Moon; Kim, Sung Su; Moon, Dea Hyun; Jeon, Byong Hun; Chang, Soon Woong
Abstract: In this study, a magnetically separable, highly active, and recyclable photocatalyst was synthesized by physico-chemical incorporation of Ag, TiO2, and Fe3 O4 into one structure. The physical and chemical properties of the catalysts were evaluated by X-ray diffraction, X-ray fluorescence spectrometry, scanning electron microscopy, field emission transmission electron microscopy, energy dispersive X-ray spectroscopy, and diffuse reflectance spectroscopy. The Ag-supported magnetic TiO2 composite demonstrated desirable properties and features such as a narrow band gap of 1.163 eV, modifiable structure, and high degradation efficiency. The activity and durability of the synthesized photocatalyst in the degradation of methyl orange (MO) in aqueous solutions under visible light irradiation and different experimental conditions were evaluated and compared to those of commercial TiO2 and Ag/TiO2 composites. It was found that the synthesized composite showed a much higher MO photodegradation efficiency than the other composites under visible light irradiation. Moreover, it exhibited a high photocatalytic activity and was recoverable and durable; its photocatalytic efficiency in MO removal was consistently higher than 93.1% after five reuses without any evident signs of deactivation. Thus, the developed photocatalyst is a very promising material for practical applications in environmental pollution remediation. Graphical abstract: Image 1 Highlights: Magnetically separable Ag/TiO2 /Fe3 O4 heterostructures were synthesized. The samples were characterized by XRD, SEM, TEM, and EDS. Magnetic Ag/TiO2 /Fe3 O4 catalyst had a lower band gap energy than TiO2 and Ag/TiO2 . The prepared catalyst showed good photocatalytic activity and high recyclability. Methyl orange was photocatalytically degraded using the synthesized catalyst.